STUDY THE STRUCTURAL AND ELECTRICAL PROPERTIES OF CdTe:Ag THIN FILMS - Mohammed, Hanaa I (Al-Nahrain Journal of Science, 2010)
The influence of silver doped n-type polycrystalline CdTe film with thickness of 200 nm andrate deposition of 0.3 nm.s-1 prepared under high vacuum using thermal co-evaporation techniqueon its some structural and electrical properties was reported. The X- ray analysis showed that allsamples are polycrystalline and have the cubic zinc blend structure with preferential orientation inthe [111] direction. Films doping with impurity percentages (2, 3, and 4) %Ag lead to asignificant increase in the carrier concentration, so it is found to change from 23.493×108 cm-3 to59.297×108 cm-3 for pure and doped CdTe thin films with 4%Ag respectively. But films dopingwith impurity percentages above lead to a significant decrease in the electrical conductivity andHall mobility, so they are found to change from 6.3×10-7(Ω.cm)-1 to 1.59 ×10-7(Ω.cm)-1 , and from16.759 ×102 cm2.(V.sec)-1 to 1.675 ×102 cm2.(V.sec)-1 respectively, for pure and doped CdTe thinfilms with 4%Ag. And also the doping lead to change the kind of conductivity for thin films obtain,so we found that pure CdTe thin film is n-type and then convert to p-type when thin film doped with (2, 3, and4) %Ag